Cytokines changes associated with electroconvulsive therapy in patients with treatment-resistant depression: a Meta-analysis. (March 2021) - Gay, F.; Romeo, B.; Martelli, C.; Benyamina, A.; Hamdani, N.
Highlights: Electroconvulsive therapy induces an initial increase of IL-6 levels Electroconvulsive therapy induces a potential decrease of TNF-α levels Electroconvulsive therapy does not change IL-4 and IL10 levels Age, gender number of ECT and depression score do not influence the course of IL-6 and TNF-α during ECT Abstract: One third of depressive patients do not achieve remission after several steps of treatment and are considered as treatment resistant. Electroconvulsive therapy (ECT) improves symptoms in 70 to 90% of such cases. Resistant depression is associated with a dysregulation of the immune system with a dysbalance between the pro- and the anti-inflammatory cytokines. Therefore, we aimed to measure the kinetic of cytokines levels before, during and at the end of ECT. To test this hypothesis, we performed a meta-analysis assessing cytokines plasma levels before, during and after ECT in patients with major depressive disorders. After a systematic database search, means and standard deviations were extracted to calculate standardized mean differences. We found that IL-6 levels increased after 1 or 2 ECT session (p = 0.01) then decrease after 4 ECT sessions (p < 0.01) with no difference at the end of ECT (p = 0.94). A small number of studies were included and there was heterogeneity across them. The present meta-analysis reveals that ECT induces an initial increase of IL-6 levels and a potential decrease of TNF-α levels. No changes on IL-4 and IL-10 levels were found. Further work is necessary to clarify the impact of ECT on peripheral cytokines.